Malignant Struma Ovarii in a Postmenopausal Asymptomatic Woman: A Case Report - Behiye Pınar Çilesiz Göksedef; Hüsnü Görgen; Şafak Yılmaz Baran (Haseki Tıp Bülteni)
Introduction: Struma ovarii is an ovarian tumor that consists predominantly thyroid tissue and accounts for only 2% of all mature teratomas. It is usually a benign condition - malignant transformation has been reported to occur in about 5% of all struma ovarii cases. Case: A 58-year-old postmenopausal woman attended our outpatient clinic for her annual gynecologic exam, on which a palpable ovary was incidentally found. Ultrasound and magnetic resonance imaging work-up showed two-centimeter solid mass on the right ovary. Laparoscopic salpingo-oophorectomy was performed; the histology report revealed a focus of thyroid papillary carcinoma in a struma ovarii. The patient underwent surgical staging procedure according to the ovarian cancer guideline. The tumor was in stage 1A, thus, no further treatment was indicated apart from follow-up. Conclusion: Malignant struma ovarii is a rare neoplasm of the ovary. Surgical staging should be included in the treatment, like in the other germ cell ovarian tumors. (The Medical Bulletin of Haseki 2011;49: 117-9